The experience of being informed of the death of a loved one by suicide: an interpretative phenomenological analysis - Pye, Naomi (2020)
Introduction. Individuals bereaved by suicide may be at an increased risk of psychological complications and their bereavement process can be influenced by interactions with professionals immediately following the death. However, there is a paucity of research into how the news of a suicide death is delivered and the impact of this. There has been a call for research to explore suicide survivors’ experiences of interactions with front line responders.